2004
DOI: 10.1248/bpb.27.1081
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Improving and Cerebral Protective Effects of Acylated Oligosaccharides in Polygala tenuifolia

Abstract: Senile dementia of the Alzheimer type and multi-infarct dementia are considered to be major problems of contemporary societies. In traditional Chinese medicine, Polygalae Radix (Japanese name: Onji), the root of Polygala tenuifolia WILLDENOW (Polygalaceae), is prescribed for amnesia, neurasthenia, palpitation, noctural emission and insomnia. 1) According to the Chinese Materia Medica, the root is guessed to have a special effect upon the will and mental powers, improving understanding and strengthening the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 19 publications
0
78
0
Order By: Relevance
“…Recent pharmacological studies have shown that P. tenuifolia could improve memory impairment caused by scopolamine, stress, glutamate, and Aβ, and promote neuronal proliferation in normal brains (Chung et al, 2002;Lin et al, 2012;Li et al, 2014). Polygalasaponins, such as polygalasaponin B, F, G, and XXXII, are the main components responsible for the action of P. tenuifolia and have been shown to improve cognitive impairment in AD effectively (Ikeya et al, 2004;Xu et al, 2009;Wu et al, 2014). However, reports have shown that polygalasaponins could be toxic to animals, leading to nose bleeding, gastrointestinal tract abnormality, and even death (Xue et al, 2009;Lin et al, 2012), which seriously limits their application and development.…”
Section: Introductionmentioning
confidence: 99%
“…Recent pharmacological studies have shown that P. tenuifolia could improve memory impairment caused by scopolamine, stress, glutamate, and Aβ, and promote neuronal proliferation in normal brains (Chung et al, 2002;Lin et al, 2012;Li et al, 2014). Polygalasaponins, such as polygalasaponin B, F, G, and XXXII, are the main components responsible for the action of P. tenuifolia and have been shown to improve cognitive impairment in AD effectively (Ikeya et al, 2004;Xu et al, 2009;Wu et al, 2014). However, reports have shown that polygalasaponins could be toxic to animals, leading to nose bleeding, gastrointestinal tract abnormality, and even death (Xue et al, 2009;Lin et al, 2012), which seriously limits their application and development.…”
Section: Introductionmentioning
confidence: 99%
“…(Polygalaceae), and has been used in traditional medicine as an expectorant, tonic, tranquilizer and antipsychotic agent (Chung et al, 1992;Huang, 1993). The dried root of this plant Pharmaceutical Biology, 2010; 48(7): 794-800 contains polygalitol, tenuigenin, polygalasaponin, oligosaccharides (Yukinobu et al, 2004) and xanthone derivatives. Recently our laboratory demonstrated antidepressant actions of the active extracted fraction YZ-50 in animal behavior despair models of mice; however, the mechanisms of its action are still unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extensive searches are being carried out for novel, naturally occurring active compounds that can be used to treat multiple-factor dementia. Numerous medicinal plant species are now being screened for advanced therapeutic drugs that possess both high efficacy and low side effects [1][2][3][4][5] . One such plant, Polygala tenuifolia Willd, is the species of interest in this study.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been renewed interest in the cognition-enhancing potential of P tenuifolia root extracts. Several studies have shown that P tenuifolia extracts have cognition improving effects in vivo, in addition to protective effects on neurotoxicity that is induced in vitro by factors such as glutamate, beta-amyloid, and the C-terminal fragment of amyloid precursor protein (CT) [2,[4][5][6] . However, the biologically active components from these extracts still require identification, and their in vivo functions and mechanisms must be understood before P tenuifolia root extracts can be developed into therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%